Editorial - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
His JIFAM volume 7 (Special Issue 3) January 2025 publishes papers related to several methods to protect the infrastructure assets as well as soil improvement methods to support the sustainable development goals for asset infrastructures management. As regulated in Indonesian Scientific Journal Accreditation, a Scientific Journal can publish the Regular, Supplement and Special Edition. The JIFAM Editorial Team express their gratitude to the authors who already submitted their papers for the seventh volume (Special Issue 3).